Large Eddy Simulation of Wind Pressure Distribution on Heterogeneous Buildings in Idealised Urban Models. (November 2015) - Mohammad, Ahmad Faiz; Zaki, Sheikh Ahmad; Ali, Mohamed Sukri Mat; Aya, Hagishima; Razak, Azli Abdul; Shirakashi, Masataka; Arai, Norio
Abstract: In a typical urban area where buildings are built in a cluster with random spacing, the distribution of the wind pressure on a building is influenced by interference effects from neighbouring buildings, which could ultimately affect the wind-induced ventilation across the building. Large-eddy simulations (LESs) were conducted for six cases of staggered random arrays with various packing densities ( λ p ). In addition, the heterogeneity of a typical urban surface was represented by buildings of different heights. Each type of building had a different aspect ratio α p (the ratio of the front area to the planar area of the building), which ranged between 0.84 (low-rise building) and 3.76 (high-rise building). The LES results showed that high-rise buildings (i.e. α p ≥ 3.0) were less obstructed from the approaching flow because they had higher aspect ratios than the low-rise buildings (i.e. α p ≤ 2.64). This was also because of their positions immediately behind the low-rise buildings. In dense arrays (i.e. λ p ≥ 0.250), the pressure drag was dominated by high-rise buildings by up to 55%. These findings will be beneficial in a study of the mean pressure distribution of clustered buildings. Although the results of this study were exclusive to random staggered arrays, they are an important addition to the existing literature on the study of wind-induced ventilation in urban areas.